Nofes on Kıtab al-Mabsut and Shems al-Eımme Abu Bakr Muhammad b. Ahmad Abu Sehl al-Sarakhsı - AKŞIT, M. Cevat (Scientific Journal of Faculty of Theology, 2007)
Abu Bakr Muhammad As-Sarakhsi is a renowned Islamic jurisprudence (fiqh) scholar from the Karahanid Turkish age (MS. IX - XIII Centuries). He authored his famous book "Al-Mabsut" dictating from his memory to the pupils from the well he had been impisoned. In his book, he includes opinions of the scholars with their basis for judgment, criticizes and discusses their counterarguments. Although Sarakhsi sfates that Al-Mabsut is an interpretation of the book Al-Mukhtasar by Hakim Al-Shehid, it appears to be an interpretation of Muhammad As-Shaybani's book Al-Asl. Examples of this have been stated in this work. There are even indications that Al-Mabsut is an original work by Sarakhsi, rather than being an interpretation of another book. Evidence of tlıis has been presented in this paper. It has been noted that social and cultııral situation of the era can be inferred from Al-Mabsut. Current printed versions of the book have been compared to various original handwritten versions. Mang tipographical errors and around 85 missing pages have been identified and reported with respective page numbers.